Templated scaffolds of cis- and trans-tetrahydrofuran gamma-amino acids: gamma-azido-beta-hydroxy-tetrahydrofuran-2-carboxylates from pentono-delta-lactones - Sanjayan, G; Stewart, A; Hachisu, S; Gonzalez, R; Watterson, M; Fleet, G (2003)
Short syntheses of enantiomeric templated scaffolds of cis- and trans-tetrahydrofuran γ-amino acids from pentono-δ-lactones derived from arabinose and ribose are reported; an unexpectedly efficient synthesis of a templated tetrahydrofuran β-amino acid by azide displacement of a triflate β to an ester function proceeds with remarkably little elimination. These materials should allow evaluation of such peptidomimetics to induce predisposition towards secondary structures. © 2003 Elsevier Ltd. All rights reserved.